Uzbek National Identity In The Translations of O‘Tkir Hoshimov’s Dunyoning Ishlari - Dildoraxon Poshshaxodjayeva (Indonesian Journal Publisher, 2026)
This study offers a comparative textual analysis of national identity representation in two translations of O'tkir Hoshimov's lyrical prose work “Dunyoning Ishlari” (1985; rev. 2015). Maya Ganina's Russian translation “Dela Zemnye” (1988) and the English co-translation “Such Is Life” (2024) by Mark Reese and Abdulloh Ruziev are examined through the lens of domestication and foreignization (Venuti, 1995; Berman, 1984; Baker, 2018). The study analyses forty-two material-cultural realia, sixty-five phraseological units, and 12 items of religious-spiritual lexis across a three-text corpus, applying dynamic equivalence theory (Nida, 1964), realia classification (Vlakhov & Florin, 1980), and translation quality assessment (House, 2015). The findings show that Ganina's Soviet-era translation follows covert domestication, producing a 43% loss rate among the fourteen high-frequency realia analysed. The Reese–Ruziev translation applies consistent foreignization, retaining 86% of the same realia through transliteration and a thirty-five-term paratextual glossary. Phonetically motivated Uzbek proverbs resist full structural transference into either target language, and Islamic formulaic expressions receive divergent treatment, reflecting each translation's ideological context. These findings advance the empirical base of Uzbek translation studies and offer practical guidance for the cross-cultural transmission of the Central Asian literary heritage